Waste incineration by-product carbon sequestration filling material and preparation method thereof
By sequestering the waste incineration fly ash and forming filler materials with other materials, the problems of low resource utilization rate and environmental risks of waste incineration by-products are solved, and filling material preparation with efficient carbonization and environmental protection benefits are achieved.
Patent Information
- Application Number
- CN202510080100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-19
AI Technical Summary
The low utilization rate of waste incineration by-product resources and its high environmental risks limit its wide application in the fields of building materials and engineering.
By mixing waste incineration fly ash with high alumina powder, L-proline and water, and introducing CO2 gas for carbonization reaction, stable carbonates are generated, thereby achieving effective carbon sequestration of fly ash. Subsequently, the treated fly mortar, waste incineration bottom slag, sulfoaluminate cement and L-histidine are stirred to form a filling material, and further carbonization and carbon solidification reaction is carried out in the goaf.
The efficient carbonization of waste incineration fly ash has been achieved, and the prepared filling materials have good compressive strength and long-term stability, and have high carbon dioxide capture capabilities, which significantly reduces greenhouse gas emissions and has significant environmental benefits.
Smart Images

Figure CN119822762A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid waste resource utilization, and specifically relates to a carbon-fixing filling material and a preparation method thereof. Background Art
[0002] The waste incineration process produces waste incineration fly ash and bottom ash. These by-products cannot be directly utilized because they contain high concentrations of chloride ions and heavy metals, and they have high environmental risks. The rich harmful substances in waste incineration fly ash make it very challenging to directly recycle and utilize. At present, waste incineration fly ash has been used in some building materials, but its practical application is still limited due to its potential environmental pollution risks and unstable performance. Similarly, waste incineration bottom ash has gradually been used to a certain extent, especially in some engineering fields, such as roadbed materials in infrastructure construction, building fillers, etc. However, the high density and instability of bottom ash still limit its application potential in a wider range of fields. Therefore, it is urgent and important to develop safe, feasible, efficient and high-value waste incineration waste resource technology.
[0003] In this context, mining filling materials, as a new type of resource utilization material, have become a potential field for the application of waste incineration waste due to their low demand for raw materials and certain performance advantages. Mining filling materials can not only reduce waste accumulation, but also effectively fill mines and improve the environment of mining areas, so they have a large room for development. Waste incineration products, especially fly ash and bottom slag, have great application potential as raw materials for filling materials. Summary of the invention
[0004] The present invention aims at the technical difficulties such as low resource utilization rate and high environmental risk of waste incineration by-products, and proposes a carbon fixation filling material and method using waste incineration by-products. The method successfully realizes the efficient carbonization of waste incineration fly ash and its application in filling materials through the innovative design of front-end carbon fixation to reconstruct fly ash particles and rear-end carbon fixation refinement structure. Specifically, the waste incineration fly ash is first mixed with high-aluminum ore powder, L-proline and water in a specific mass ratio to form a uniform fly ash slurry. Then, by introducing CO2 gas, a carbonization reaction is carried out to promote the alkaline substances in the fly ash to react with CO2 to form stable carbonates, thereby achieving effective carbon fixation of the fly ash. Next, the treated fly ash slurry, waste incineration bottom ash, sulphoaluminate cement and L-histidine are stirred to form a filling material, and finally filled into the goaf, and the carbon fixation reaction is further realized in the goaf, completing the carbonization and carbon fixation process of the front and back stages. The obtained filling material not only has good compressive strength and long-term stability, but also exhibits a high carbon dioxide capture capacity, effectively reduces greenhouse gas emissions, and has significant environmental benefits. This technology can not only effectively replace traditional mineral resources and provide an economical and environmentally friendly solution for mining and filling operations, but also provide a feasible path for the resource utilization of waste incineration fly ash, and has broad application prospects.
[0005] The present invention aims to solve the above-mentioned technical problems and provides a method for preparing a carbon-fixing filling material using waste incineration by-products.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A garbage incineration byproduct carbon fixation filling material and method thereof, the method comprising the steps of:
[0008] (1) Mix waste incineration fly ash, high aluminum ore powder, L-proline and water in proportion, set the stirring speed to 500 r / min, form a uniform waste incineration fly ash slurry, and store it in a mixing tank A;
[0009] (2) introducing lime kiln flue gas with a CO2 concentration of 20% Vol into the mixing tank A, and maintaining the carbonization reaction for 5 minutes at the initial CO2 flow rate; then, maintaining the CO2 flow rate, and continuing to maintain the carbonization reaction for 5 minutes, and finally obtaining slurry A;
[0010] (3) Sulphoaluminate cement, waste incineration ash, slurry A in the mixing tank A and L-histidine are transported to the mixing tank B in proportion, the stirring speed is set to 300 r / min, and the stirring time is set to 10 min to prepare filling material B;
[0011] (4) The filling material B prepared in the mixing tank B is transported to the goaf. A CO2 pipeline is provided at the bottom of the goaf. During the solidification process of the filling material, industrial flue gas with a CO2 concentration of 20% Vol is continuously introduced into the goaf through the CO2 pipeline to obtain the carbon-fixing filling material.
[0012] In the technical solution of the present invention: in step (1), the proportions of waste incineration fly ash, high aluminum ore powder, L-proline and water are 10-40 parts by mass, 10-40 parts by mass, 0.5-1.2 parts by mass and 50 parts by mass, respectively.
[0013] In the technical solution of the present invention: in step (2), the initial flow rate of CO2 is set to 0.2-1.0Nm 3 / h; then, the flow rate increased to 0.5-1.5Nm 3 / h.
[0014] In the technical solution of the present invention: in step (3), the proportions of sulphoaluminate cement, waste incineration ash, slurry A in the mixing tank A and L-histidine are 5-10 parts by mass, 30-50 parts by mass, 45-70 parts by mass and 0.5-1.0 parts by mass, respectively.
[0015] In the technical solution of the present invention: in step (3), the particle size of the garbage incineration bottom ash is 0.5-1 mm.
[0016] In the technical solution of the present invention: in step (4), the injection flow rate of CO2 is set at 0.8-1.5Nm 3 / h.
[0017] In the technical solution of the present invention: in step (4), the injection time of CO2 is set at 30-120 minutes.
[0018] In the technical solution of the present invention: in step (4), the CO2 pipe is made of PVC material and has an inner diameter of 100-150 mm.
[0019] The beneficial effects of the present invention are as follows:
[0020] (1) The present invention utilizes the synergistic effect of carbon dioxide gas and L-proline to precisely control the mineral structure of waste incineration fly ash, successfully achieves its reconstruction, and generates a reconstructed material with amorphous calcium carbonate as the main component. Carbon dioxide plays a key role in this process, reacting with calcium-rich minerals in fly ash to convert into highly reactive amorphous calcium carbonate, significantly improving the physicochemical activity of fly ash.
[0021] (2) The present invention introduces high-aluminum ore powder as an auxiliary material and uses waste incineration ash as aggregate to cleverly regulate the dynamic chemical balance between the aluminum phase and carbonate ions, thereby effectively regulating the formation process of insoluble complex salt minerals. The regulation of this reaction mechanism enhances the reactivity of reconstructed fly ash and other materials. A small amount of sulfoaluminate cement plays a catalytic role in this system, promoting the formation of calcium sulfonate ore phase in a relatively low alkalinity environment, further accelerating the hydration and gelling reaction, and significantly improving the mechanical strength and structural stability of the filling material.
[0022] (3) After the filling material is pumped into the goaf, it undergoes a second carbonization reaction. L-histidine acts as a carbonization crystal form regulator in this process, promoting the further carbonization transformation of the residual calcium-containing mineral phase in the high-fluidity filling material to generate nano-scale calcium carbonate mainly composed of aragonite. This reaction not only optimizes the microstructure of the material and significantly fills the voids, but also greatly improves the density and compactness of the filling material, thereby enhancing its mechanical stability and anti-permeability performance.
[0023] (4) Compared with the traditional filling material processing method, the filling material prepared by the present invention exhibits multiple advantages: first, the material has excellent mechanical properties, especially in the development of early strength, which provides a reliable bearing capacity guarantee for the construction process; second, through the dual effects of gel adsorption and carbonate solidification mechanism, the material can effectively reduce the dissolution of heavy metals, improve environmental friendliness, and meet strict environmental protection standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The production process of carbon-fixing filling materials from waste incineration by-products.
[0025] Figure 2 Comparison of X-ray diffraction analysis of filling materials in some embodiments.
[0026] Figure 3 Infrared spectrum analysis of filling materials in some comparative examples and embodiments. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto:
[0028] Example 1
[0029] (1) First, waste incineration fly ash, high aluminum ore powder, L-proline and water are mixed in a mass ratio of 40:10:0.5:50 to form a uniform waste incineration fly ash slurry, which is then stored in a mixing tank A.
[0030] (2) The stirring speed of the stirring tank A is set to 500 r / min, and the lime kiln flue gas with a carbon dioxide concentration of 20% Vol is introduced. In the initial stage, the flow rate of CO2 is set to 0.5 Nm 3 / h, and the carbonization reaction was maintained for 5 min; then, the flow rate was increased to 1.0 Nm 3 / h, and continue to maintain the carbonization reaction for 5 minutes to finally obtain slurry A.
[0031] (3) Sulphoaluminate cement, waste incineration ash, slurry A in mixing tank A and L-histidine were transported to mixing tank B in a mass ratio of 5:30:65:0.5, the stirring speed was set to 300 r / min, and the stirring time was set to 10 min to prepare filling material B.
[0032] (4) The filling material B prepared in the mixing tank B is transported to the filling device and then transported to the goaf in the mine by pumping. A thin carbon dioxide pipeline is installed at the bottom of the goaf filling system. During the solidification process of the filling material, industrial flue gas with a carbon dioxide concentration of 20% Vol is continuously introduced. The injection flow rate of CO2 is set at 0.8Nm 3 / h and continue for 60min to obtain a carbon-fixed filling material.
[0033] Example 2
[0034] The raw materials and test methods used in this example are the same as those in Example 1.
[0035] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that in step (1), the waste incineration fly ash, high aluminum ore powder, L-proline and water are mixed in a mass ratio of 30:20:1.2:50.
[0036] Example 3
[0037] The raw materials and test methods used in this example are the same as those in Example 1.
[0038] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that the flow rate of CO2 in step (2) is set to 1 Nm 3 / h, and the carbonization reaction was maintained for 5 min; then, the flow rate was increased to 1.5 Nm 3 / h, and continue to maintain the carbonization reaction for 5 minutes to finally obtain slurry A.
[0039] Example 4
[0040] The raw materials and test methods used in this example are the same as those in Example 1.
[0041] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that the flow rate of CO2 in step (2) is set to 0.2 Nm 3 / h, and the carbonization reaction was maintained for 5 min; then, the flow rate was increased to 0.5 Nm 3 / h, and continue to maintain the carbonization reaction for 5 minutes to finally obtain slurry A.
[0042] Example 5
[0043] The raw materials and test methods used in this example are the same as those in Example 1.
[0044] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that in step (3), sulphoaluminate cement, waste incineration ash, slurry A in mixing tank A and L-histidine are transported to mixing tank B in a mass ratio of 5:20:75:0.5.
[0045] Example 6
[0046] The raw materials and test methods used in this example are the same as those in Example 1.
[0047] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that in step (3), sulphoaluminate cement, waste incineration ash, slurry A in mixing tank A and L-histidine are transported to mixing tank B in a mass ratio of 10:50:40:1.
[0048] Example 7
[0049] The raw materials and test methods used in this example are the same as those in Example 1.
[0050] The steps for preparing the filling material in this embodiment are different from those in Embodiment 1 in that in step (4), industrial flue gas with a carbon dioxide concentration of 20% Vol is continuously introduced, and the injection flow rate of CO2 is set at 1.5 Nm 3 / h and continue for 30min.
[0051] Example 8
[0052] The raw materials and test methods used in this example are the same as those in Example 7.
[0053] The steps for preparing the filling material in this embodiment are different from those in Embodiment 7 in that in step (4), lime kiln flue gas with a carbon dioxide concentration of 20% Vol is continuously introduced, and the injection flow rate of CO2 is set at 1.5 Nm 3 / h and continue for 120min.
[0054] Comparative Example 1
[0055] (1) First, waste incineration fly ash and water are mixed in a mass ratio of 50:50 to form a uniform waste incineration fly ash slurry, which is then stored in a mixing tank A.
[0056] (2) Sulphoaluminate cement, natural aggregate, and slurry A in mixing tank A were transported to mixing tank B in a mass ratio of 5:30:65, and the stirring speed was set to 300 r / min and the stirring time was set to 10 min to obtain a filling material.
[0057] Comparative Example 2
[0058] (1) First, waste incineration fly ash, high aluminum ore powder, L-proline and water are mixed in a mass ratio of 40:10:0.5:50 to form a uniform waste incineration fly ash slurry, which is then stored in a mixing tank A.
[0059] (2) The stirring speed of the stirring tank A is set to 450r / min, and the lime kiln flue gas with a carbon dioxide concentration of 20% Vol is introduced. In the initial stage, the flow rate of CO2 is set to 0.5Nm 3 / h, and the carbonization reaction was maintained for 5 min; then, the flow rate was increased to 1.0 Nm 3 / h, and continue to maintain the carbonization reaction for 5 minutes to finally obtain slurry A.
[0060] (3) Sulphoaluminate cement, natural aggregate, slurry A in mixing tank A and L-histidine were transported to mixing tank B in a mass ratio of 5:30:65:0.5, the stirring speed was set to 300 r / min, the stirring time was set to 10 min, and a filling material was prepared.
[0061] Comparative Example 3
[0062] (1) First, waste incineration fly ash, high aluminum ore powder, L-proline and water are mixed in a mass ratio of 40:10:0.5:50 to form a uniform waste incineration fly ash slurry, which is then stored in a mixing tank A.
[0063] (3) Sulphoaluminate cement, waste incineration ash, slurry A in mixing tank A and L-histidine were transported to mixing tank B in a mass ratio of 5:30:65:0.5, the stirring speed was set to 300 r / min, and the stirring time was set to 10 min to prepare filling material B.
[0064] (4) The filling material prepared in the mixing tank B is transported to the filling device and then pumped to the goaf in the mine. A thin carbon dioxide pipeline is installed at the bottom of the goaf filling system. During the solidification process of the filling material, lime kiln flue gas with a carbon dioxide concentration of 20% Vol is continuously introduced. The injection flow rate of CO2 is set at 0.8Nm 3 / h and continue for 60min to obtain the filling material.
[0065] The X-ray diffraction patterns of the filling materials prepared in some embodiments and comparative examples are as follows: Figure 2 As shown in the graph, it can be seen that the main alkaline components such as Ca(OH)2 and Ca(Cl)O in the waste incineration fly ash treated by this method undergo significant chemical transformation and transform into various crystalline calcium carbonates, including amorphous calcium carbonate, calcite, nepheline and aragonite. With the change of the additive dosage, Figure 2 It can be clearly observed that the production of aragonite crystals with high specific surface area, high surface roughness and high reactivity has increased significantly. This phenomenon shows that additives play a key role in regulating the morphology and properties of calcium carbonate crystals, and can effectively promote the formation of aragonite crystals and enhance the reactivity of materials through their unique crystal structure.
[0066] The infrared spectra of the filling materials prepared in some embodiments and comparative examples are as follows: Figure 3 As shown. Figure 3 Analysis shows that the CO stretching vibration characteristic peaks (approximately at 1400 cm -1 This change indicates that during the treatment process, the carbon dioxide absorption inside the system has been significantly improved, and the morphology of calcium carbonate has changed significantly. In particular, during the conversion of calcium carbonate, the generation of aragonite crystals has been further enhanced, indicating that this method can effectively promote the carbonization reaction of alkaline components and control the morphology of calcium carbonate crystals.
[0067] The mechanical property test results of the filling materials prepared in each embodiment and comparative example are listed in Table 1. It can be seen from the test data that the unconfined compressive strength of the filling materials prepared in comparative examples 1-3 is less than 0.5MPa, while the unconfined compressive strength of the filling materials treated by this method is significantly improved. In the first step of carbonization, the alkaline minerals of the waste incineration fly ash react to form a mineral phase mainly composed of amorphous calcium carbonate. This process not only improves the physicochemical activity of the material, but also provides a stable matrix for subsequent reactions. At this stage, although the high-aluminum ore powder does not directly participate in the reaction, it plays a role of uniform dispersion through sufficient mixing, creating favorable conditions for subsequent multiphase reactions. In the mixing stage, the high-aluminum ore powder reacts synergistically with the waste incineration bottom ash to release active silicon and aluminum sources, providing the necessary chemical basis for the material to form the initial structure. Subsequently, a small amount of sulphoaluminate cement introduced catalyzes the formation of calcium sulfonate mineral phases in a low alkalinity environment. These mineral phases are filled in the initial pore structure, effectively improving the compactness of the material and accelerating the hydration and gelation reaction. In addition, L-histidine, as a surfactant in the system, not only promotes the further carbonization transformation of residual calcium-based minerals, but also helps to generate nanoscale calcium carbonate mainly composed of aragonite. These nanoscale particles further fill and strengthen the microstructure of the material, thereby significantly improving the density and mechanical properties of the material. However, the results also show that the higher the CO2 flux, the better. Excessive CO2 will destroy the structural integrity of the initial hydrated gel, resulting in a decrease in the strength of the material.
[0068] Table 1 Mechanical properties of filling materials (MPa)
[0069]
[0070] After curing for 7 days, the prepared filling material was subjected to a heavy metal leaching test using the toxicity characteristic leaching procedure (TCLP), and the test results are shown in Table 2. As can be seen from the data, the heavy metal leaching concentrations of the filling materials prepared in Comparative Examples 1-3 are all higher than the relevant national standard limits, indicating that the materials without optimization treatment have a greater environmental risk. In contrast, the filling materials of the embodiments treated by this method show a significant heavy metal curing effect, and their heavy metal leaching concentrations are all lower than the national standard limits, meeting the requirements for safe use. This improvement is mainly attributed to the optimized design of material components and microstructures in this method. During the reaction process, the calcium carbonate generated by the carbonization reaction not only provides a higher material density, but also significantly reduces the migration channel of heavy metals through physical blocking. At the same time, the introduction of alkaline environment and active silicon aluminum source induces the formation of secondary mineral phases such as calcium sulfonate, which effectively fixes the heavy metal ions in the system through chemical coordination and ion exchange. In addition, the generation of aragonite nano-calcium carbonate further fills the material micropores and enhances the long-term stability of the curing system to heavy metals.
[0071] Table 2 Heavy metal leaching content of filling materials (mg / L)
[0072]
[0073] The filling material preparation method provided by the present invention realizes the large-scale application of waste incineration fly ash, while ensuring that the obtained filling material exhibits excellent performance in mechanical properties and heavy metal leaching control, meeting the strict requirements of actual engineering applications.
[0074] Finally, the above specific embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A garbage incineration byproduct carbon fixation filling material and a preparation method thereof, characterized in that: The method comprises the following steps: (1) Mix waste incineration fly ash, high aluminum ore powder, L-proline and water in proportion, set the stirring speed to 500 r / min, form a uniform waste incineration fly ash slurry, and store it in a mixing tank A; (2) introducing lime kiln flue gas with a CO2 concentration of 20% Vol into the mixing tank A, and maintaining the carbonization reaction for 5 minutes at the initial CO2 flow rate; then, maintaining the CO2 flow rate, and continuing to maintain the carbonization reaction for 5 minutes, and finally obtaining slurry A; (3) Sulphoaluminate cement, waste incineration ash, slurry A in the mixing tank A and L-histidine are transported to the mixing tank B in proportion, the stirring speed is set to 300 r / min, and the stirring time is set to 10 min to prepare filling material B; (4) The filling material B prepared in the mixing tank B is transported to the goaf. A CO2 pipeline is provided at the bottom of the goaf. During the solidification process of the filling material, industrial flue gas with a CO2 concentration of 20% Vol is continuously introduced into the goaf through the CO2 pipeline to obtain the carbon-fixing filling material.
2. The method according to claim 1, characterized in that In step (1), the ratios of the waste incineration fly ash, the high-aluminum ore powder, the L-proline and water are 10-40 parts by mass, 10-40 parts by mass, 0.5-1.2 parts by mass and 50 parts by mass respectively.
3. The method according to claim 2, characterized in that In step (2), the initial flow rate of CO2 is in the range of 0.2-1.0 Nm 3 / h; the CO2 maintains a flow rate range of 0.5-1.5Nm 3 / h.
4. The method according to claim 3, characterized in that In step (3), the ratios of sulphoaluminate cement, waste incineration ash, slurry A in the mixing tank A and L-histidine are 5-10 parts by mass, 30-50 parts by mass, 45-70 parts by mass and 0.5-1.0 parts by mass, respectively.
5. The method according to claim 4, characterized in that In step (3), the particle size of the waste incineration ash is 0.5-1 mm.
6. The method according to claim 5, characterized in that In step (4), the flow rate of lime kiln flue gas with a CO2 concentration of 20% Vol into the goaf is 0.8-1.5 Nm 3 / h.
7. The method according to claim 6, characterized in that In step (4), lime kiln flue gas with a CO2 concentration of 20% Vol is introduced into the goaf for 30-120 minutes.
8. The method according to claim 7, characterized in that In step (4), the CO2 pipe is made of PVC and has an inner diameter of 100-150 mm.
9. A garbage incineration byproduct carbon fixation filling material, characterized by: The filling material is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing mine underground filling curing agent from solid waste residues
CN115557760A
Preparation method of carbamate coating solution for inducing rapid carbonization of cement-based material
CN118495991A